Micro milling cutting forces on machining aluminum alloy - Araujo, Anna Carla; Mougo, Adriane Lopes; Campos, Fabio de Oliveira (8th International Conference on MicroManufacturing (ICOMM 2013), 2013)
Miniaturization has increased over the last decade and, as a consequence, manufacturing of micro parts for bioengineering and aerospace applications are one of the areas there is a need of research and development. Micro milling is a flexible machining process that allows the fabrication of high quality parts. This article compares mechanistic models for micro milling process considering homogeneous grain properties. It is not taken into account dynamic behavior of tool and intersection between tool-workpiece due to stiffness or grain variation. Experimental data is used to calculate specific pressure in different approaches and compare results between models. The specific pressure considered based on previous articles is over estimated, as values around 2kN/mm2 is calculated from experiments.
Keywords: micro milling; mechanistic models; cutting forces